Mapping the potential risk of climate change to South Africa's health sector: An analysis of the Health Risk and Vulnerability Assessment Tool developed for the South African health sector - Weaver, Zachariah (School of Economics, 2023)
Health Risk and Vulnerability Assessments are key resources for national health departments to understand how to properly prepare for the impact of climate change on a country's health sector. However, countries often lack the required estimates of future burden of disease and of health services to undertake these assessments. This thesis examines the development and application of a Health Risk and Vulnerability Assessment Tool built by OneWorld Sustainable Investments for the South African National Department of Health to develop an understanding of the risk of climate change to the South African health sector by addressing the lack of estimates of future burden of disease and of health services. The thesis examines how the Tool was developed, and was able to build capacity on the impact of climate change on the South African health sector among district health officials, capture their estimates of future burden of disease and of health services to calculate the risk of climate change to the health sector, and then present the resulting risk data in an easy to understand and approachable manner for health officials to integrate into their climate change adaptation planning work.